Taste-Based Gender Favouritism in High-Stake Decisions: Evidence from the Price is Right - Dana, Jason; Klein Teeselink, Bouke; Atanasov, Pavel (Oxford University Press, 2024)
Gender discrimination is present across various fields,but identifying the underlying mechanism is challenging. We demonstrate own-gender favouritism in a field setting that allows for clean identification of tastes versus beliefs: the One Bid game on the TV show The Price Is Right. Players must guess an item's value without exceeding it,leaving the last bidder with a dominant 'cutoff' strategy of overbidding another player by $ 1. We show that last bidders are significantly more likely to cut off opposite-gender opponents. This behaviour is explained by own-gender favouritism rather than beliefs that cutting off opposite-gender opponents is more profitable. © 2023 The Author(s). Published by Oxford University Press on behalf of Royal Economic Society.
Keywords: decision analysis; gender discrimination; ideology; price dynamics; strategic approach; ODS 5 - Igualdad de género; ODS 10 - Reducción de las desigualdades